2014
DOI: 10.1007/s00213-014-3841-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cannabinoid system in anterior cingulate cortex and orbitofrontal cortex modulates cost-benefit decision making

Abstract: Despite the evidence for altered decision making in cannabis abusers, the role of the cannabinoid system in decision-making circuits has not been studied. Here, we examined the effects of cannabinoid modulation during costbenefit decision making in the anterior cingulate cortex (ACC) and orbitofrontal cortex (OFC), key brain areas involved in decision making. We trained different groups of rats in a delay-based and an effort-based form of cost-benefit T-maze decision-making task. During test days, the rats rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 86 publications
2
27
0
Order By: Relevance
“…Other experimental data likewise point to a plausible role for prefrontal CB 1 receptors, particularly within the ACC, in mediating the deleterious effects of THC on effort-based cost-benefit decision-making. 10 Inactivating the ACC decreased choice of HR trials on both the rCET used here, as well as a decision-making paradigm in which costs are physically rather than cognitively effortful. 22,32 Stimulation of this region in humans can also elicit feelings of endeavour and "gearing up" for an effortful challenge.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Other experimental data likewise point to a plausible role for prefrontal CB 1 receptors, particularly within the ACC, in mediating the deleterious effects of THC on effort-based cost-benefit decision-making. 10 Inactivating the ACC decreased choice of HR trials on both the rCET used here, as well as a decision-making paradigm in which costs are physically rather than cognitively effortful. 22,32 Stimulation of this region in humans can also elicit feelings of endeavour and "gearing up" for an effortful challenge.…”
Section: Discussionmentioning
confidence: 78%
“…Cannabis derivatives alter human choice behaviour in laboratory decision-making tasks involving delay or risk costs, and similar impairments have been observed in animal models following administration of THC or related cannabinoid agonists. [9][10][11][12] While physical effort-based decision-making has recently been shown to be sensitive to cannabinoid receptor activation, 10 it is unknown whether decisions involving cognitive effort costs are likewise susceptible. The distinction is important; these 2 forms of decisionmaking are subserved by dissociable neurobiological mech anisms, and cognitive costs are more representative of J Psychiatry Neurosci 2017;42(2) the effort costs faced in an industrialized society.…”
Section: Introductionmentioning
confidence: 99%
“…A number of brain regions and cerebral interconnections have been described to be involved in predecisional processing and planning actions: parietal-frontal circuits, anterior cingulate and orbitofrontal cortices, and hippocampus 19,20. These cerebral areas and others are also activated during the pain experience; they belong to the pain matrix and have been shown to be deactivated by APAP as described by a recent functional magnetic resonance imaging study 18,21.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor involved in predecisional processing is the endocannabinoid system. The role of cannabinoid signaling in decision-making pathways and frontal cortical circuits of decision making has been recently studied 20. The authors showed in rats that the activation of the cannabinoid system in anterior cingulate and orbitofrontal cortices, two brain regions with a high prevalence of cannabinoid-1-receptors, modulates decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, administration of WIN 55, 212-2, a synthetic CB 1 -prefering agonist, did not affect delay-based choice in the same task (Pattij et al, 2007), demonstrating that phyto- and synthetic cannabinoids with similar actions at the CB 1 receptor can produce divergent behavioural effects. In contrast, direct infusions of arachidonyl-2-chloroethylamide (ACEA), a potent synthetic CB 1 receptor agonist, into the orbitofrontal cortex (OFC) produced a robust shift towards the low reward option on a T-maze equivalent of the operant delay-discounting task (Khani et al, 2015). This effect is similar to that observed following post-training lesions of the OFC on the same task, and might suggest that presynaptic intra-OFC CB 1 receptor activation induces decision-making deficits by dampening glutamate release in this region (Rudebeck et al, 2006).…”
Section: Cannabinoid Modulation Of Prefrontal Cortical Function: Fmentioning
confidence: 99%